Locations Ranking using Page Rank Algorithm - A. Al-Sultany, Ghaidaa; A. Abd Al-Ameer, Asraa (International Journal of Engineering and Technology, 2018)
Nowadays, large amount of user-generated data can obtained from social media (e.g., Instagram and Flicker) .People sharing their travel experiences with geo-tagged photo through these media, and the photo itself has important information like title, tags and location.Thesetypes of data provide a new perspective for us to understand the contexts of users. In this paper we focused on tourism service by collecting and analyzing geo-tagged photo from the social media to identify the most popular tourist places and rank them based on user location. We used PageRank algorithm that rank locations based on the relation between the locations and a set of tags that discovered by weighting scheme. Thus, an intelligent location-based tourist services can be provide to people. The work experiments have shown encouraging results in terms of ranking the given locations.Â Â
Keywords: Geo-tags resources; Social media data; Information ranking; Tourist attraction; Smart cultural tourism